Explicit optimal hysteretic damper design in elastic-plastic structure under double impulse as representative of near-fault ground motion. (2016) - Shiomi, Takuma; Fujita, Kohei; Tsuji, Masaaki; Takewaki, Izuru
A closed-form maximum elastic-plastic response is derived for a structure with hysteretic dampers under the critical double impulse as a representative of near-fault ground motion. It is shown that the classification into nine cases is possible depending on the combination of elastic-plastic responses of the structure and the hysteretic damper and the double impulse enables the derivation of the closed-form maximum elastic-plastic critical response of the controlled structure by using the energy balance in each case. It is demonstrated that the closed-form maximum elastic-plastic critical response is quite useful for finding an optimal hysteretic damper quantity depending on the input level of the double impulse.